The entrance of modern optics to Ottoman science - Pekkendir, Sena. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2015., 2015)
In Ottoman State, modern sciences were brought into the country as a result of military targets. The first engineering schools were being established from the beginning of 18th century and foreigner scholars were brought in, to provide the transmission of knowledge. Also a comprehensive translation movement from the West was initiated. One of the pioneers of this movement, Chief Instructor of the Imperial School of Military Engineering, Ishak Efendi (d. 1836), wrote a treatise in Ottoman named Mecmua-i Ulum-i Riyaziye (Istanbul 1247-1250/1831-1834) using European resources. Mecmua-i Ulum-i Riyaziye is the first encyclopedia of positive sciences in Ottoman State and the first comprehensive study to represent positive sciences systematically. It’s also credited for its presentation of Western European optical knowledge to Ottoman science properly. This study aims to examine the process of the entrance of modern optics to Ottoman State. Firstly, it presents the development of the science of optics from the ancient ages to the 18th century in order to present the back ground of the modern optical thought. Then, it focuses on the innovations in Ottoman State and the process of the entrance of modern sciences into the country. It examines the chapters of Mecmua-i Ulum-i Riyaziye on optics in order to track down the transmission of optical knowledge from West to Ottoman State and it examines the literature of Optical Work provided by Ottoman scholars. The study concludes in 1937, when modern concepts of optics were introduced into the country by Refik Fenmen.
Keywords: Science -- Turkey.; Optics.